O Estágio supervisionado como espaço de reflexão na formação inicial de professores: uma análise a partir de um curso de Licenciatura em Ciências Biológicas - Correia, Emike Luzia Pereira (Universidade Federal de São Carlos, 2019)
The main objective of this work was to understand the reflexive formation of a group of graduates in the context of an Discipline of internship, seeking to identify the contents and central themes brought in their reflections. To achieve the proposed objective, we conducted a qualitative research, allied to the case study methodology, using the participant observation technique and document analysis of various materials produced within the discipline, which were: memorial narrative, reflective diary, replanning, questionnaire and discipline assessment. Thus, we understand that during the internship period, undergraduates became involved in reflective processes, overcoming superficial views and moving towards in-depth and critical understandings of some aspects of teaching practice. By analyzing the reflections brought by the undergraduates, we identified some methodological strategies that stood out as potential for the reflective development, such as: memorial narrative, reflective diary, moments of exchanges and discussions in the internship classes at the university and the dynamics of replanning. The results presented here reinforce the importance that teacher training courses provide spaces for graduates to reflect on their experiences and the teaching profession, surpassing uncritical views and moving towards a more reflective and critical posture during their professional performance.
Supervised internship as a space for reflection in initial teacher education: an analysis from a degree course in Biological Sciences
Keywords: Formação inicial; Professor reflexivo; Initial formation; Supervised internship; Reflective teacher; Estágio supervisionado; CIENCIAS HUMANAS::EDUCACAO